Monetary Condition Index - Dicko, Oumar (Université d'Ottawa | University of Ottawa, 2017)
The Monetary Conditions Index (MCI) is calculated from a linear combination of the short-run interest rate and the exchange rate. It is a weighted average of short term interest rate and exchange rate vis-à-vis their value in a base period. The weights reflect the relative effects of the respective MCI components on aggregate demand. The Bank of Canada used it as its operational target for monetary policy but moved away from it and stopped publishing it in 2006, mainly due to issues with the construction and interpretation of the MCI. In this paper we have calculated the MCI with the new Canadian-Dollar Effective Exchange Rate Index (CERI) from 1987 to 2017. We found that the CERI MCI behaved similarly with the Bank of Canada MCI. Our analysis of the CERI MCI over the period from 1987 to 2017 led us to the conclusion that the Bank of Canada decision to move away from the MCI as an operational target was justified. Although, the Bank of Canada should have continued publishing the MCI since the MCI can provide timely insights on the state of monetary conditions and inflation predictions when used in conjunction with other indicators.